Atividade antiulcerogênica e anti-inflamatória intestinal do isômero (-)-fenchona em modelos animais - Araruna, Maria Elaine Cristina (2022)
Monoterpenes are secondary metabolites present in several medicinal species. (-)-fenchone is a monoterpene present in the plant species Foeniculum vulgare (fennel), Thuja occidentalis L. (tuja) and Lavandula stoechas (lavender). Pharmacological studies point to its antiinflammatory, antioxidant, gastroprotective, antidiarrheal and antifungal effects. Thus, the present study aimed to evaluate its anti-duodenal ulcer, healing gastric and intestinal antiinflammatory activity in animal models. Oral administration (p.o) of (-)-fenchone at all doses evaluated (37.5; 75; 150 and 300 mg/kg) reduced (p<0.001) the ulcerative lesion area (ALU) in duodenum of rats subjected to cysteamine-induced injuries. From the model of gastric ulcer induced by acetic acid, toxicity was investigated by repeated doses for 14 days. The results showed that treatment with (-)-fenchone at a dose of 150 mg/kg (p.o) reduced (p<0.001) ALU when compared to the control group. This effect was related to an increase in the levels of GSH, SOD, IL-10 (p<0.001) and TGFβ (p<0.01) and a reduction (p<0.001) in the levels of MDA, MPO, IL-1β, TNF-α and NFκB. The administration of (-)-fenchone for 14 days did not change the weight of the organs (heart, liver, spleen and kidneys), nor the biochemical and hematological parameters. It was also observed that the test substance protects the animals from the reduction of water and feed consumption. In the TNBS-induced acute induction model of intestinal inflammation, (-)-fenchone at all doses (37.5; 75; 150 and 300 mg/kg, v.o.) reduced (p<0.05) the lesion score macroscopic examination, ALU, weight/length ratio and diarrheal index. The intestinal anti-inflammatory effect was also evaluated in a subchronic model of relapsing ulcerative colitis. (-)-fenchone at its best dose (150 mg/kg) reduced (p<0.01) the macroscopic lesion score, ALU and colonic weight/length ratio. In colon samples from the acute and sub-chronic models it was shown that at its best dose (150 mg/kg) it reduced (p<0.001) the levels of MDA and MPO and restored the levels of GSH and SOD. In addition, it reduced (p<0.001) the levels of IL-1β, TNF-α and and NFκB, as well as increased the levels of TGFβ (p<0.001) and restored (p<0.01) those of IL-10. In the study of the intestinal cyprotective mechanism, an increase (p<0.001) of immunostaining for zone of occlusion-1 (ZO-1) was shown. Thus, these data suggest that (-)-fenchone presents anti-duodenal ulcer activity, gastric healing activity related to the induction of lesion re-epithelialization and low toxicity by repeated doses. And intestinal anti-inflammatory activity in the acute and subchronic phases, being related to the cytoprotection of the intestinal barrier through the preservation of gap junctions. These effects also involve the participation of the antioxidant system and immunomodulation.